Exemplifying EFL Madura Scholars’ Tenets on The Inclusive Cultures of Inner Circle in ELT - Roziyan Adi Wicaksana; Budyi Suswanto (Technium Social Sciences Journal, 2023)
This study set out to discover what cultures of inner circle (IC) meant to EFL Scholars in their English lessons. Thirty-three Management department Scholars were chosen using the convenience sample approach (henceforth, participants). They were required to complete a series of questions and explain their responses. According to the study’s findings, the participants’ tenet systems were considered to be intricate. Three distinct enunciates of the Inclusive Inner Circle in their English courses provides evidence for this; 70% of participants agreed, 19% disagreed, and 11% were neutral about the inclusive culture of inner circle. At the conclusion of this essay, suggestions for more research are provided.